EVALUASI KELONGSORAN PADA RUAS JALAN WELERI – PATEAN KM50 DAN ALTERNATIF PENANGANANNYA - Moh. Ariawan Hidayat; Danni Tanro; Sri Prabandiyani Retno Wardani; Indrastono Dwi Atmanto (Jurnal Karya Teknik Sipil, 2013)
Road between Weleri - Patean is a national road that has an important role in regional and national economic development. The road is an alternative route that connects the “Pantura” to the “Selatan” route. In January 2012, there was a catastrophic landslide occurred in kilometers 50 from Weleri to Patean. It’s 6.8 meters in height and 8 meters in lenght landslide. As result,, only half the roads are passable by vehicles, and by the implementation of on way system, the flow of traffic became pretty slow. After slope stability analysis using Fellenius method is performed, it is shown that the SF or safety factor of the slope is 0.878 and for 1.284 by using Plaxis V.8.2 program. Both SF less than normal safety factor which is 1.3. So it can be inferred that the slope is in critical condition. Therefore, it is very important to install special reinforcement to restrain or stabilize the slope. The first alternative of slope reinforcement is gabion, the second alternative is retaining wall and the third alternative is steel sheet pile reinforcement. Based on finite element method calculation using Plaxis V.8.2 software, it is found that gabion changes the safety factor of the slope from 1.284 to 1.512 and gives  4.645 cm displacement. Meanwhile, retaining wall increases the value of safety factor from 1.284 to 1.538 and gives 4.365 cm displacement. In otherhand, steel sheet pile reinforcement gives a noticeable safety factor value which is 2.075 and gives 2.932 cm displacement. Compared to the other alternatives, steel sheet pile reinforcement performs the best stabilization reinforcement, resulting in high safety factor value and small displacement value, therefore, steel sheet pile reinforcement is is considered as the best alternative solutions for landslide in Weleri – Patean Km 50 Road.